Detailed Account of Complexity for Implementation of Circuit-Based Quantum Algorithms - Cardoso, Fernando R.; Akamatsu, Daniel Yoshio; Campo Junior, Vivaldo Leiria; Duzzioni, Eduardo I.; Jaramillo, Alfredo; Villas-Boas, Celso J. (Frontiers in Physics, 2021)
In this review article, we are interested in the detailed analysis of complexity aspects of both time and space that arises from the implementation of a quantum algorithm on a quantum based hardware. In particular, some steps of the implementation, as state preparation and readout processes, in most of the cases can surpass the complexity aspects of the algorithm itself. We present the complexity involved in the full implementation of quantum algorithms for solving linear systems of equations and linear system of differential equations, from state preparation to the number of measurements needed to obtain good statistics from the final states of the quantum system, in order to assess the overall complexity of the processes.